PENGARUH MANAJEMEN BERBASIS KINERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA DAN AKUNTABILITAS PEMERINTAH DAERAH (Studi Empiris pada Pemerintah Kabupaten Sleman) - , ANDRI PERMANA DIPUTR ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Starting at the mid-1980s, public sector management changes quite dramatically from the traditional management system became a model of public sector management and more flexible to accommodate the market. The Changes in public sector management is called New Public Management approach. The implications of such a paradigm shift in the management is the arrangement of the Indonesian government that focuses on changes to performance-based management, which is a part of the reform era of New Public Management. This study aimed to find empirical evidence of the influence of performance-based management that consists of clear objectives, performance measurement, reward and transformational leadership on performance and accountability of the Government of Sleman District. This study used a mixed method design, with explanatory sequential design. Explanatory sequential design is method who composed of two phases, sequential explanatory research design begins with a quantitative method which is the Stuctural Equation Model (SEM) method with the approach of variance (partial least squares path modeling), then after getting the results, the next step is follow-up the results of research with qualitative methods using thematic content analysis. The results of this study indicate that the objectives are clear and measurable significant positive effect on performance and accountability. Performance measurement also has a significant positive effect on the performance of qualitative and accountability, but the measurement of performance is not significant positive effect on quantitative performance. Reward didnât significant positive effect on the performance of the Government of Sleman district, both quantitative and qualitative performance. The results of next hypothesis proved that the reward significant positive effect on accountability. Transformational leadership also has a significant positive effect on the performance and accountability of the Government of Sleman district. Based on the research and discussion is also found that the application of performance-based management practices in government of Sleman District, is quite heavily influenced by Institutional Theory.